2016
DOI: 10.3346/jkms.2016.31.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Following Hip and Knee Replacement Arthroplasty in Korea: A Nationwide Study Based on Claims Registry

Abstract: The aim of this study was to examine the incidence and trends of clinically relevant venous thromboembolism (VTE) including deep vein thrombosis (DVT) and pulmonary embolism (PE) after hip and knee replacement arthroplasty (HKRA) in Korea. Between January 1 and December 31, 2010, 22,127 hip replacement arthroplasty (HRA) patients and 52,882 knee replacement arthroplasty (KRA) patients were enrolled in the analysis using the administrative claims database of the Health Insurance Review and Assessment Service (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
3
35
4
Order By: Relevance
“…The VTE incidence was 0.6% in the rivaroxaban cohort in this study, which was similar with that observed in the study with the pooled data of four RECORD clinical trials, which showed that the incidence of symptomatic VTE in rivaroxaban-treated patients 18 The incidence of VTE following hip arthroplasty in this study was lower than that of Lee et al, 19 which investigated the VTE incidence in a Korean population that underwent hip replacement arthroplasty with chemoprophylaxis using the HIRA database. The study showed the incidence of VTE, DVT, and PE as 7.0%, 5.1%, and 2.5%, respectively, which was higher than that observed with chemoprophylaxis (2.0%, 1.4%, and 0.9%, respectively).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The VTE incidence was 0.6% in the rivaroxaban cohort in this study, which was similar with that observed in the study with the pooled data of four RECORD clinical trials, which showed that the incidence of symptomatic VTE in rivaroxaban-treated patients 18 The incidence of VTE following hip arthroplasty in this study was lower than that of Lee et al, 19 which investigated the VTE incidence in a Korean population that underwent hip replacement arthroplasty with chemoprophylaxis using the HIRA database. The study showed the incidence of VTE, DVT, and PE as 7.0%, 5.1%, and 2.5%, respectively, which was higher than that observed with chemoprophylaxis (2.0%, 1.4%, and 0.9%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…The study showed the incidence of VTE, DVT, and PE as 7.0%, 5.1%, and 2.5%, respectively, which was higher than that observed with chemoprophylaxis (2.0%, 1.4%, and 0.9%, respectively). 19 The reported incidence was significantly higher than that in our present study. The different inclusion criteria of patient population of this study might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The use of pharmacologic prophylaxis combined with mechanical prophylaxis is recommended by the clinical guidelines of the American Academy of Orthopaedic Surgeons (AAOS) clinical guidelines . However, the routine use of pharmacologic prophylaxis in Asian patients is still controversial because of an increased risk of bleeding due to pharmacologic agents and variable incidences of VTE, ranging from 1.8% to 35.7%, when mechanical prophylaxis alone was used . Previous history of VTE is a known indication for more potent anticoagulants, but other risk factors that require pharmacologic prophylaxis after TKA are not clearly defined in the Asian population …”
Section: Introductionmentioning
confidence: 99%
“…1 However, the routine use of pharmacologic prophylaxis in Asian patients is still controversial because of an increased risk of bleeding due to pharmacologic agents and variable incidences of VTE, ranging from 1.8% to 35.7%, when mechanical prophylaxis alone was used. [2][3][4][5] Previous history of VTE is a known indication for more potent anticoagulants, but other risk factors that require pharmacologic prophylaxis after TKA are not clearly defined in the Asian population. 6 Hemostasis and inflammation are linked; therefore, surgical trauma-related perioperative inflammatory state increases blood coagulability.…”
Section: Introductionmentioning
confidence: 99%